2022
DOI: 10.3390/jpm12091484
|View full text |Cite
|
Sign up to set email alerts
|

Association of Inflammatory and Metabolic Biomarkers with Mitral Annular Calcification in Type 2 Diabetes Patients

Abstract: (1) Background: Type 2 diabetes mellitus (T2DM) contributes to cardiovascular disease and related mortality through the insidious effects of insulin resistance and chronic inflammation. Mitral annular calcification (MAC) is one such degenerative process promoted by T2DM. (2) Methods: This is a post hoc analysis of insulin resistance, inflammation, and hepatic steatosis markers in T2DM patients without atherosclerotic manifestations, but with incidental echocardiographic detection of mild MAC. (3) Results: 138 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Diabetes mellitus is the main risk factor for progression to severe PAD, with chronic limb-threatening ischemia or even amputations [36][37][38][39]. In our study, independent of gender, we found a higher prevalence of diabetes mellitus among women, associated with a higher proportion of injuries (with a severity of more than 50% and 70%), as well as a higher proportion of cases with severe injuries or amputations.…”
Section: Discussionsupporting
confidence: 58%
“…Diabetes mellitus is the main risk factor for progression to severe PAD, with chronic limb-threatening ischemia or even amputations [36][37][38][39]. In our study, independent of gender, we found a higher prevalence of diabetes mellitus among women, associated with a higher proportion of injuries (with a severity of more than 50% and 70%), as well as a higher proportion of cases with severe injuries or amputations.…”
Section: Discussionsupporting
confidence: 58%
“…A recent meta-analysis found that those with a sedentary lifestyle had a 23% higher risk of cardiovascular mortality and a 17% higher risk of incident cardiovascular disease than those who achieved the recommended 150 min of moderate physical activity per week [ 54 ]. Physical inactivity, together with diabetes mellitus, and a family history of early coronary artery disease were found to be significant independent predictors of unexpected MI [ 55 ]. Regarding the correlation between alcohol use and ACS, Tersalvi et al, observed that heavy drinkers (>2 drinks/day) had about a 40% higher rate of in-hospital mortality and MACE (a combined outcome of in-hospital reinfarction, stroke, and/or death by any cause) than light drinkers (2 drinks/day) [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Atrial flutter and fibrillation, as well as AV block and sinus tachycardia, might also result from myocardial ischemia, left ventricular systolic and/or diastolic dysfunction, pulmonary embolism, acute respiratory distress syndrome and even a direct action of the virus upon the conduction system. 191 , 199 …”
Section: Ecg Features In Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 99%
“…Atrial flutter and fibrillation, as well as AV block and sinus tachycardia, might also result from myocardial ischemia, left ventricular systolic and/or diastolic dysfunction, pulmonary embolism, acute respiratory distress syndrome and even a direct action of the virus upon the conduction system. 191,199 Supraventricular arrhythmias are also frequently documented in COVID-19 patients. A recent systematic review and meta-analysis revealed a 10.3% prevalence of overall ECG abnormalities among COVID-19 patients.…”
Section: Dovepressmentioning
confidence: 99%